O Colégio Pedro II e o ensino secundário brasileiro: 1930-1961 - Massunaga, Magda Rigaud Pantoja (1989)
The aim of this work is to examine Pedro II School as the official institution designed to be the model for the secondary schools in Brazil, as well as its implications as a model during the period from 1930 to 1961. The effort to make secondary schools uniform dates back to the days of' the Empire; hence the creation of a school to serve as a model for all the others. However, Brazil' s great dimensions and variety of economic and cultural aspects, as well as the expansion of the number of secondary schools, made such uniformity impossible to be achieved. As a model institution , Pedro II School was given the adequate conditions to develop proper pedagogical work. It was also given such prerogatives as the elaboration of the teaching programs to be adopted by all of the secondary schools in the country and the presence of some of its members in official organs related to teaching and education.